2019
DOI: 10.1111/1365-2656.13037
|View full text |Cite
|
Sign up to set email alerts
|

The sex‐determination pattern in crocodilians: A systematic review of three decades of research

Abstract: Sex in crocodilians is not determined by chromosomes, but by egg incubation temperature, where different temperatures produce different clutch sex ratios. Two patterns have been proposed to describe these changes in sex ratios: a 100% female proportion at low and high temperatures with male predominance at intermediate ones (FMF) or a simpler pattern with a single female‐to‐male transition (FM). Over the last three decades, researchers have provided empirical information to support either of these two patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
0
24
1
Order By: Relevance
“…Very little is known regarding how thermal reaction norms vary across parental genotypes and populations in crocodilians. A systematic review of studies reporting temperatureby-sex reaction norms in crocodilians found evidence for latitudinal variation in the reaction norm of A. mississippiensis (González et al, 2019). In particular, populations appear to vary in the range of male-promoting temperatures, with higher-latitude populations exhibiting a wider range of malepromoting temperatures (González et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known regarding how thermal reaction norms vary across parental genotypes and populations in crocodilians. A systematic review of studies reporting temperatureby-sex reaction norms in crocodilians found evidence for latitudinal variation in the reaction norm of A. mississippiensis (González et al, 2019). In particular, populations appear to vary in the range of male-promoting temperatures, with higher-latitude populations exhibiting a wider range of malepromoting temperatures (González et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies reporting temperatureby-sex reaction norms in crocodilians found evidence for latitudinal variation in the reaction norm of A. mississippiensis (González et al, 2019). In particular, populations appear to vary in the range of male-promoting temperatures, with higher-latitude populations exhibiting a wider range of malepromoting temperatures (González et al, 2019). While intriguing, such observations should be interpreted with caution because many of the studies examined were conducted prior to the discovery that the thermosensitive period of this species begins much earlier than previously thought, opening up the possibility that incubation temperatures prior to egg collection may have accounted for a proportion of the observed variation in sex ratios (McCoy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] In fact, the thermal window producing males is narrow in crocodiles and no constant temperature produces 100% males in most crocodile species. [ 56 ] The same is true for the highly studied leopard geckos Eublepharis macularius . [ 57 ] It was argued that instead of being detrimental, female‐biased adult sex ratios might be in fact advantageous from the point of view of population reproductive potential.…”
Section: Adaptive Values Of Gsd and Esd: Is Esd A Short‐lived Strategy?mentioning
confidence: 85%
“…For each species remaining, we searched using “incubat*” and the species name to try and find additional studies reporting hatching success at extremely warm temperatures, but no additional estimates were found. Because crocodilians were underrepresented in our data set ( n = 0 species), we used literature reviewed by González et al (2019) to add additional studies. For two species ( Alligator mississippiensis and Caiman crocodilus ), hatching success was not provided for each temperature within the OTR but was described generally (e.g., hatching success was “greater than 90%” at all temperatures).…”
Section: A Quantitative Review Of Reptile Embryo Heat Tolerancementioning
confidence: 99%
“…Both can increase nest temperatures in detrimental ways (Dayananda & Webb, 2017; Hall & Warner, 2018; Tiatragul, Hall, & Warner, 2020). Historically, reptiles have served as a primary model in studies of thermal developmental plasticity (Warner, Du, & Georges, 2018; While et al, 2018), which has resulted in a large body of literature (reviewed by González et al, 2019; Howard, Bell, & Pike, 2014; Noble, Stenhouse, & Schwanz, 2018; Pezaro, Doody, & Thompson, 2017; Refsnider, Clifton, & Vazquez, 2019; Warner et al, 2018; While et al, 2018) upon which researchers can draw to predict species responses to rising temperatures; however, there are currently no standard assays for measuring heat stress of reptile embryos (unlike post‐hatching stages; Angilletta, Zelic, Adrian, Hurliman, & Smith, 2013). Such methods are critical to understand the evolution and ecology of embryo heat tolerance and predict responses to global change.…”
Section: Introductionmentioning
confidence: 99%